Isotropic fluid structures and role of non-metricity on their dynamics governed by an electric charge: A theoretical study - Tayyab Naseer; M. Sharif; M. Waqas; J. Andrade; Ahmed Emara (PLoS ONE, 2026)
This research explores the dynamics of compact stellar objects characterized by the Kohler-Chao-Tikekar and Tolman IV spacetimes under the effects of an electric charge within the framework of f ( Q ) gravity, where Q indicates the non-metricity. We start our analysis with the assumption of a static spherical line element and formulate the field equations corresponding to an isotropic interior fluid setup. We then construct two novel solutions under the two above-mentioned metrics which involve multiple unknown constants. These constants are calculated using junction conditions at the boundary, where we match our interior solutions with the exterior Reissner-Nordström line element. Afterwards, we analyze specific conditions that must be met to ensure the feasibility of compact models in real-world applications. The graphical analysis is performed under a particular star candidate, namely LMC X-4 with several choices of the considered model parameters. Under certain chosen values, our results show that both stellar solutions are in good agreement with the physically existence criterion. In light of the current findings, we deduce that our work significantly advances the understanding of how the interior fluid dynamics of compact stars are influenced by the symmetric teleparallel gravity, offering vital information for further research in astrophysics.